Hormonal regulation of mango fruit ripening - Sakimin, Siti Zaharah (Curtin University, 2011)
Mango fruit ripen quickly. It is highly perishable. Short shelf life of mango fruit limits its transportation to distant domestic and international markets. The objective of my research was to elucidate the role of changes in endogenous levels of brassinosteroids (BRs), ethylene, abscisic acid (ABA) and/or indole-3-acetic acid (IAA) in modulating the ripening processes of 'Kensington Pride' mango fruit. The endogenous levels of these regulators were regulated using inhibitors of their biosynthesis and/or action to unfold their mechanism in delaying/hastening mango fruit ripening, extending storage life and improving fruit quality as well as to underpin the mode of action of ABA and NO in modulating ethylene biosynthesis and activities of fruit softening enzymes in the pulp during ripening and/or alleviating chilling injury (CI) during cool storage.Higher endogenous level of ABA at the climacteric-rise stage triggered the climacteric peak of ethylene production coupled with a significant quadratic relationship between both of them; suggest that ABA play a key role in modulating mango fruit ripening. The exogenous application of ABA (1.0 - 2.0 mM) promoted skin colour development and fruit softening during ripening, and the trend was reversed with its inhibitor of biosynthesis - nordihydroguaiaretic acid (0.1 - 0.2 mM NDGA). The endogenous level of IAA was higher at the initial stage of ripening and decline over ripening period. The exogenous application of 45 - 60 ng g-1 FW Epi- BL increased the climacteric peak of ethylene and respiration, promoted skin colour, but the changes in the endogenous level of BRs (castasterone and brassinolide) are unlikely to modulate mango fruit ripening as it is present in a trace amounts in mango pulp tissues throughout the ripening period.Exogenous postharvest application of ABA (1.0 mM) increased the climacteric peak of ethylene production through promoting the activities of 1- aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS), ACC oxidase (ACO) enzymes, and ACC content, decreased the fruit firmness with increased exopolygalacturonase (exo-PG), endo-PG and endo-1,4-_-D-glucanase (EGase) activities, decreased pectinesterase (PE) activity in the pulp, higher total sugars and sucrose, advanced degradation of total organic acids, citric and fumaric acid. The application of 0.2 mM NDGA showed reverse trends for these ripening indicator parameters.NO fumigation (20 μL L-1 or 40 μL L-1) was more effective in delaying fruit ripening when applied at the pre-climacteric (PC) stage, than at the climacteric-rise (CR) stage. NO (20 μL L-1) fumigation delayed and suppressed the endogenous ethylene production, activities of ACS and ACO enzymes, and ACC content, rate of respiration, higher pulp rheological properties (firmness, springiness, cohesiveness, chewiness, adhesiveness, and stiffness) with lower activities of exo-, endo-PG, EGase, but maintained higher PE activity in pulp tissues during ripening at 21°C and cool storage (13°C). NO treatments (20 and 40 μL L-1) significantly alleviated CI index during ripening at ambient temperature following 2- or 4-week of cold-stored (5°C) period. All NO fumigation treatments significantly suppressed ethylene production and respiration rates irrespective of cold storage period. NO–fumigated with above 5 μL L-1 significantly delayed fruit softening up to 2 days and retarded colour development, reduced total sugar and fructose concentrations, increased tartaric and shikimic acid at fully ripe stage during ripening period irrespective of cold-stored fruit.In conclusion, the higher levels of endogenous IAA in fruit pulp during the PC stage and the accumulation of ABA prior to the climacteric stage might switch on ethylene production that triggers fruit ripening. There is a significant quadratic relationship between endogenous level of ABA in the pulp and ethylene production during fruit ripening period. Exogenous Epi-BL promoted fruit ripening, whilst, the changes in endogenous levels of BRs are unlikely to modulate mango fruit ripening. Moreover, the exogenous application of ABA (1.0 mM) promoted the activities of ethylene biosynthesis enzymes (ACS and ACO) and ACC content and ethylene biosynthesis as well as endo-PG activity in the pulp, whilst, the NDGA-treated fruit showed the reverse trends. The application of NO fumigation (20 L L-1) at PC stage can be effectively used to delay the fruit ripening up to 2 days at ambient temperature (21°C) and cool-storage (13°C) through suppression the activity of ethylene biosynthesis and softening enzymes and alleviate CI following 2- and 4-week cold storage (5°C) without any adverse effects on fruit quality.